(untitled) (Revista Argentina de Musicología, 2019)
Psychology of music is a discipline built on the alliance between Musicology and Experimental Psychology emerging towards the second half of the nineteenth century. This alliance coincides, then, with the expansion of Western Europe and its totalizing perspective of knowledge based on modern science. This paper aims to argue that for this reason, the psychology of music is foundationally ethnocentric. This bias generates conditions of epistemic injustice, mainly by making invisible the nature of musical experiences located in contexts epistemologically different from those of Western music, denying epistemic sovereignty to the subject of experience. In order to exemplify this bias, three axioms of the psychology of music are discussed: the autonomy of the sound, the division of musical experience into three different praxes (audition, performance and composition), and the use of basic categories coming from Western music theory. These three axioms are discussed in terms of the effects they have on the descriptions of the musical experience. Finally, some aspects of the epistemic injustice linked to the subject of knowledge and to the conditions of production of academic knowledge are discussed.